Respuesta :
Answer:
The required polynomial is f(x)=[tex]2x^{3}-3x^{2}+3x+7[/tex]
Step-by-step explanation:
Given that polynomial is passing through points (-1,-1) (0,7) ( 1,9) and (2,17)
Let, The required polynomial be f(x)=[tex]ax^{3}+bx^{2}+cx+d[/tex]
For point (-1,-1)
f(x)=[tex]ax^{3}+bx^{2}+cx+d[/tex]
f(-1)=[tex]a(-1)^{3}+b(-1)^{2}+c(-1)+d[/tex]
(-1)a+b-c+d=(-1) Equation 1
For point (0,7)
f(x)=[tex]ax^{3}+bx^{2}+cx+d[/tex]
f(0)=[tex]a(0)^{3}+b(0)^{2}+c(0)+d[/tex]
d=7 Equation 2
For point ( 1,9)
f(x)=[tex]ax^{3}+bx^{2}+cx+d[/tex]
f(1)=[tex]a(1)^{3}+b(1)^{2}+c(1)+d[/tex]
a+b+c+d=9 Equation 3
For point (2,17)
f(x)=[tex]ax^{3}+bx^{2}+cx+d[/tex]
f(2)=[tex]a(2)^{3}+b(2)^{2}+c(2)+d[/tex]
8a+4b+2c+d=17 Equation 4
Replacing value of d of equation 2 in equation 1,3,4
For equation 1:
(-1)a+b-c+d=(-1)
(-1)a+b-c=(-8)
For equation 3:
a+b+c+d=9
a+b+c=2
For equation 4:
8a+4b+2c+d=17
8a+4b+2c=10
Now,
On adding equation 1 and 3
For equation 1: (-1)a+b-c=(-8)
For equation 3: a+b+c=2
((-1)a+b-c)+(a+b+c)=(-8)+2
2b=(-6)
b=(-3)
Replacing value of b in equation 1 and 4:
For equation 1: (-1)a+b-c=(-8)
(-1)a+(-3)-c=(-8)
(-1)a-c=(-5) Equation 4
For equation 4: 8a+4b+2c=10
8a+4b+2c=10
8a+4(-3)+2c=10
8a+2c=22 Equation 5
For value of a and c:
Equation 4 can be write as
(-1)a-c=(-5)
a+c=5
a=5-c
Replacing value of a in equation 5
8a+2c=22
8(5-c)+2c=22
40-8c+2c=22
-6c=-18
c=3
So,
a=5-c=5-3=2
a=2
Thus,
The value of
a=2, b=(-3), c=3 and d=7
The required polynomial is
f(x)=[tex]ax^{3}+bx^{2}+cx+d[/tex]
f(x)=[tex]2x^{3}-3x^{2}+3x+7[/tex]
![Ver imagen mintuchoubay](https://us-static.z-dn.net/files/d7d/b227839c45e80d499c641c2dd9f82e30.png)